FEITOSA, Cleyton. 2017. Políticas Públicas LGBT e Construção Democrática no Brasil. Curitiba: Appris. - Émerson Silva Santos (Universidade do Estado do Rio de Janeiro, 2019)
Reseña: FEITOSA, Cleyton. 2017. Políticas Públicas LGBT e Construção Democrática no Brasil. Curitiba: Appris.